CODIFICATION OF PROPERTY LAW IN SERBIA - Аchievements and prospects - - Cvetić, Radenka Milorad (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
After the Serbian Civil Code came out of force, property law in Serbia has not been systematically regulated. A number of statutory lacunae, a long-term practice of inadequate regulatory acts for property relations, poor quality of certain regulations, overwhelming number of pieces of legislation where property legal norms have been scattered, brought about the legal uncertainty in matters of property law. The most prospective solution for the given problem would be a new civil code or a new statute (code) which would comprehensively regulate property law. Despite the fact that these problems and the need to codify property law have been known, and that solutions have been advocated together with some efforts to achieve them, no significant progress has been made. The reason might be far simpler than it could seem at the first glance.